Strategy of Religious Character Implementation for Special Needs Student at SD Langit Biru Kota Bengkulu - Hartati, Merri Sri; Hardiansyah; Nanang Edi Hariyanto; Eka Nur Septioningrum (International Journal of Basic Educational Research, 2024)
This article examines the strategies used by teachers in integrating religious character for children with special needs at the research location at SD Langit Biru Kota Bengkulu. The aim of this research is to present a reference/learning model for children with special needs which is still very rarely found in research on education. This happens because there are still very few schools that are serious about working on inclusive class programs. Of these few schools, SD Langit Biru, Kota Bengkulu is one of the schools that holds inclusion classes. The method used in this research is descriptive qualitative with a case study approach. Data collection techniques through interviews, observation and documentation. In data analysis, content analysis is used where the results of documentation, interviews and observations are compiled, edited or interpreted .. The results of this research are: First, there are three types of needs of ABK students at SD Langit Biru, Kota Bengkulu, namely, speech delay, Grahita, and Autism. Second , there is no standard character development strategy for children with special needs. Learning strategies are adapted to the type of special needs and are stated in each individual program and according to the achievements of the phases in the independent curriculum. Third, although each has its own individual program. The four obstacles faced by teachers include a lack of knowledge about children with special needs, fluctuating parental commitment and limited facilities. Although this research is a case study in one elementary school and it is very possible that different strategies will be found in other schools, this article presents strategies and learning models in cultivating religious character for children with special needs which can be a reference in developing other learning strategies.